IMPACT OF TRADE POLICIES FROM THE STAKEHOLDER PERSPECTIVE: A CASE STUDY OF CAR MANUFACTURING INDUSTRIES IN MALAYSIA - Murad Ahmad, Abdul (International Journal of Supply Chain Management, 2018)
Through facilitative efforts by AFTA, the Malaysian government has entered into trade agreements with other ASEAN member states. The current body of literature provides a general understanding of the effects of trade policies on developing nations, but it does not provide specifics, such as how those trade policies affect a given industry or even a specific developing nation. The purpose of this study was to explore the effects of the AFTA trade liberalization policies on Malaysia s automotive industry. A case study was conducted using the triangulation of empirical statistical data collected from secondary sources, an analysis of policy documents, and from qualitative interviews conducted with consumers, automotive industry workers, and experts in the automotive industry or in the realm of policy analysis and trade politics. The Malaysian government entered into trade agreements out of a desire to protect domestic industry, with a focus on protecting the automotive industry. However, these trade agreements have not always worked in Malaysia s favour, and the country has experienced challenges as a result of the trade policies in the region. While economic growth has been high for the past several decades, the automotive industry is still developing, and the country is still classified as a developing nation. Results indicated that consumers had the lowest level of awareness of these policies even though they were some of those that were the highest effected because of the implementation of those policies. Synthesis of data from the analysed interviews indicated that the results of Malaysia s entry into AFTA on the automotive industry have been both deep and far reaching, but that no one group is aware of all of the effects of those trade agreements, or that the trade agreements have resulted in positive changes for the country as a whole. Keywords Malaysia, automotive sector, stakeholder perspectives